Metal‐Free Synthesis of Pyrimidine and Naphthoquinone‐Fused Pyrroles from Arylglyoxal‐Based Domino Reactions. Issue 14 (7th April 2023) - Panday, Anoop Kumar; Ali, Danish; Parvin, Tasneem; Choudhury, Lokman H.
Abstract: Herein we report acid mediated two and three‐component domino reactions of cyclic enamines such as 2‐amino‐1, 4‐naphthoquinone, and 6‐amino‐1, 3‐dimethyluracil with arylglyoxals for the synthesis of diverse fused pyrroles. The two‐component reaction of arylglyoxal and 2‐amino‐1, 4‐naphthoquinone in the acetic acid medium provided substituted naphthoquinone‐fused pyrroles tethered with hydroxyl and aryl substituents. On the other hand, under similar reaction conditions, the reaction of phenylglyoxal with 6‐amino‐1, 3‐dimethyluracil provided an unusual bipyrrolopyrimidine with a quaternary carbon center following a domino reaction involving the formation of five new sigma bonds in one‐pot. Interestingly, the reaction of arylglyoxals with 6‐amino‐1, 3‐dimethyluracil in ethanol medium in the presence of 10‐mol% PTSA provided a three‐component product having pyrimidine fused pyrrole linked with 6‐aminouracil moiety. We have also developed a three‐component reaction of 2‐amino‐1, 4‐naphthoquinone, arylglyoxals, and 4‐hydroxy‐1‐methylquinolin‐2(1H)‐one for the synthesis of naphthoquinone‐fused pyrroles linked with hydroxyquinoline derivatives. Abstract : Herein we report two and three‐component domino reactions of arylglyoxals with cyclic enamines, 2‐amino‐1, 4‐naphthoquinone and 6‐aminouracil derivatives for the synthesis of structurally diverse fused pyrroles.